The Development of the Principle of Dominus Litis as a Foundation for Ethics and Professionalism in Prosecution at the Prosecutor's Office - Hudha Bagus Setyadi; Ali Masyhar Mursyid; Cahya Wulandari (Jurnal Ilmu Sosial dan Humaniora, 2025)
This article discusses the development of the principle of dominus litis as a foundation for ethics and professionalism in prosecution at the Prosecutor's Office. The principle of dominus litis, which positions prosecutors as controllers of cases, plays an important role in Indonesia's criminal justice system. This research employs a normative legal approach by analyzing existing regulations and prosecutorial practices carried out by the Prosecutor's Office. The findings indicate that strengthening prosecutors' authority within the context of dominus litis not only enhances the effectiveness of law enforcement but also contributes to the formation of ethics and professionalism in prosecution. Thus, the principle of dominus litis becomes a crucial foundation for realizing justice that is oriented towards public interests and fulfilling human rights